Correction: A scoping review on the health effects of smoke haze from vegetation and peatland fires in Southeast Asia: Issues with study approaches and interpretation. - PLOS ONE Staff (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0274433.].